Can Students’ Self-Efficacy Beliefs Explain Academic Motivation And Career Intentions? - Wimmer, Anna-Kathrin (Technological University DublinTechnological University Dublin ARROW@TU Dublin, 2023)
In our technologized and increasingly complex world, jobs in STEM make a crucial contribution to innovation and sustainability. However, there are still many vacancies in this field. To tackle the shortage of professionals, it is even more important to successfully prepare qualified young people for engineering careers and foster competences that promote innovative and creative solutions. In addition to cognitive abilities, research has shown how self-efficacy, which describes confidence in one's own abilities to successfully overcome obstacles, can influence students’ motivation, interest and therefore academic and vocational training success. Studies show that people with a strong belief in their own competence have greater persistence in completing and problem-solving tasks. Hence, this paper discusses how the students’ own perception of self-efficacy can influence their interest in the subject, academic retention, and subsequent career intentions and success. To gain further empirical insights, data from the mixed-methods study “digiMINT” will be collected using narrative interviews with female pupils, STEM students and employees, as well as industry representatives. The aim is to understand conditions of engineering education and jobs, and additionally the perception of self-efficacy as a predictive factor of career intentions. Furthermore, it will be evaluated how self-efficacy can be cultivated as a valuable skill in engineering education and teaching additionally to cognitive skills. In long term, promoting a positive experience for students’ own selfefficacy could support a sustainable integration into the labor market and equip future engineers with an interdisciplinary which is particularly relevant for complex tasks in an increasingly complex world.
Keywords: MINT; 300 Sozialwissenschaften; STEM; self-efficacy; academic performance; Motivation; MINT; Karriereplanung; Kreativität; Selbstwirksamkeit; Kompetenzen